Geomatic techniques for utilities consumption analysis in urban areas during emergency periods - Zollini, Sara; Alicandro, Maria; Dominici, Donatella (GEOmedia, 2023)
This paper has the main purpose of proposing a methodology to understand the occupation of parking spots by using the synergy of different geomatic techniques. Aerial, satellites, and UAV data are studied through the OBIA to analyse, by change detection, the main differences pre-, during and post-lockdown due to Covid-19. The first results are really promising and pave the ground for a future automation of the proposed procedure. The results can be also integrated in BIM and GIS to help the management of utilities consumption in emergency periods, and they create a dataset to enhance and increase consumption efficiency in residential areas.